1975
DOI: 10.1029/wr011i001p00144
|View full text |Cite
|
Sign up to set email alerts
|

Drainage of groundwater resting on a sloping bed with uniform rainfall

Abstract: The differential equation derived by Childs for groundwater flow over a sloping bed, the streamlines being assumed to be parallel to the slope, is integrated for the case of ditches and uniform rainfall. Expressions are obtained for the maximum vertical water table height, the location of this maximum and of the watershed, and the water table shape. Calculated water table heights are in much better agreement with previously published experimental data than those calculated from an earlier theory based on the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

1987
1987
2019
2019

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 5 publications
0
23
0
Order By: Relevance
“…The physically inappropriate solution of Schmid and Luthin (1964) best fits the numerical data for the maximum pressure head ( m ) expressed as the ratio L/ m but not phreatic height. The Towner (1975) solution gave the best fit to the numerical results for both the height of the phreatic surface and the location of the maximum on the slope. This suggests that in design of drains on slopes that Schmid and Luthin (1964) would be the best analytical solution if the pressure head on the impermeable boundary is required, but the Towner solution will be best if the water-table height is the required value.…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations
“…The physically inappropriate solution of Schmid and Luthin (1964) best fits the numerical data for the maximum pressure head ( m ) expressed as the ratio L/ m but not phreatic height. The Towner (1975) solution gave the best fit to the numerical results for both the height of the phreatic surface and the location of the maximum on the slope. This suggests that in design of drains on slopes that Schmid and Luthin (1964) would be the best analytical solution if the pressure head on the impermeable boundary is required, but the Towner solution will be best if the water-table height is the required value.…”
Section: Discussionmentioning
confidence: 86%
“…However, Fig. 7b shows that the phreatic surface height, from the simulations, is very closely modelled by the Towner (1975) and Chapman (1980) solutions. The Wooding and Chapman (1966) solution underestimates L/ h m when 位 > 1.…”
Section: Comparison Of Analytical and Numerical Solutionsmentioning
confidence: 80%
See 2 more Smart Citations
“…They found that flow through an inclined soil slab that has a length-to-thickness ratio greater than 10:1 could be accurately represented by a one-dimensional, slopeparallel flow model. Childs (1971) and Towner (1975) give analytic solutions for steady-state, unconfined, slopeparallel flow both with and without recharge. Chauan and others (1968) and Ram and Chauan (1987) present analytic solutions for the problem of transient slope-parallel flow between two trenches on a slope with constant recharge.…”
Section: A Mathematical Model For Hillside Flow Modified Dupuit Flowmentioning
confidence: 99%